Identification of novel Legionella genes required for endosymbiosis in Paramecium based on comparative genome analysis with Holospora spp. Issue 11 (14th August 2018) - Watanabe, Kenta; Suzuki, Haruo; Nishida, Takashi; Mishima, Manami; Tachibana, Masato; Fujishima, Masahiro; Shimizu, Takashi; Watarai, Masahisa
ABSTRACT: The relationship between Legionella and protist hosts has a huge impact when considering the infectious risk in humans because it facilitates the long-term replication and survival of Legionella in the environment. The ciliate Paramecium is considered to be a protist host for Legionella in natural environments, but the details of their endosymbiosis are largely unknown. In this study, we determined candidate Legionella pneumophila genes that are likely to be involved in the establishment of endosymbiosis in Paramecium caudatum by comparing the genomes of Legionella spp. and Holospora spp. that are obligate endosymbiotic bacteria in Paramecium spp. Among the candidate genes, each single deletion mutant for five genes (lpg0492, lpg0522, lpg0523, lpg2141 and lpg2398) failed to establish endosymbiosis in P. caudatum despite showing intracellular growth in human macrophages. The mutants exhibited no characteristic changes in terms of their morphology, multiplication rate or capacity for modulating the phagosomes in which they were contained, but their resistance to lysozyme decreased significantly. This study provides insights into novel factors required by L. pneumophila for endosymbiosis in P. caudatum, and suggests that endosymbiotic organisms within conspecific hosts may have shared genes related to effective endosymbiosis establishment. Abstract : We determined candidate Legionella pneumophila genes that are likely to be involved in the establishment of endosymbiosis in Paramecium caudatum by comparing the genomes of Legionella spp. and Holospora spp.